Clear-Cell Myomelanocytic Tumor of Ligamentum Teres Hepatis - Ergün, Sefa; Akıncı, Ozan; Çomunoğlu, Nil; Kocael, Ahmet (Cerrahpaşa Medical Journal, 2021)
Clear-cell myomelanocytic tumor (CCMT) of falciform ligament/ligamentum teres hepatis is a very uncommon lesion described as a variant of perivascular epithelioid cell tumor (PEComa), which includes smooth muscle cells, blood vessels, and express melanocytic and smooth muscle markers. Most patients are asymptomatic or have nonspecific gastrointestinal symptoms, and the tumors are usually found incidentally. The origin and definitive diagnosis of the CCMT can be made by histopathological examination of the specimen after the surgical excision. PEComas express HMB45, HMSA-1, Melan A, Mart 1, microphtalmia transcription factor (Mitf), actin, and less desmin. In this case report, we presented our first experience with a CCMT of ligamentum teres hepatis. Cite this article as: Ergün S, Akıncı O, Çomunoğlu N, Kocael A. Clear-Cell Myomelanocytic Tumor of Ligamentum Teres Hepatis. Cerrahpaşa Med J 2021; 45(1): 57-59.